2023
DOI: 10.1167/jov.23.12.7
|View full text |Cite
|
Sign up to set email alerts
|

Spatial contextual cues that help predict how a target will accelerate can be used to guide interception

Emily M. Crowe,
Jeroen B. J. Smeets,
Eli Brenner

Abstract: Objects in one's environment do not always move at a constant velocity but often accelerate or decelerate. People are very poor at visually judging acceleration and normally make systematic errors when trying to intercept accelerating objects. If the acceleration is perpendicular to the direction of motion, it gives rise to a curved path. Can spatial contextual cues help one predict such accelerations and thereby help interception? To answer this question, we asked participants to hit a target that moved as if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Previous research has shown that people commit significant estimation errors in interaction with accelerating objects (e.g., Refs. [ [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] ]), suggesting that pedestrians’ perception is biased in a safety-threatening fashion. Therefore, the goal of this study was to investigate whether a simple visual signal that binarily indicates that an approaching vehicle is accelerating can improve TTC estimation so that overestimation is reduced, thereby increasing traffic safety.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that people commit significant estimation errors in interaction with accelerating objects (e.g., Refs. [ [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] ]), suggesting that pedestrians’ perception is biased in a safety-threatening fashion. Therefore, the goal of this study was to investigate whether a simple visual signal that binarily indicates that an approaching vehicle is accelerating can improve TTC estimation so that overestimation is reduced, thereby increasing traffic safety.…”
Section: Introductionmentioning
confidence: 99%